Sequestro e transferência da proteína Cry1F do milho em Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae) e implicações para organismos não alvo - Souza, Camila da Silva Fernandes (2017)
One of the main problems with the use of Bt is the ability of target insects to evolve resistance to toxic proteins, in addition the potential risk to non-target organisms.Therefore the goal of this work was evaluate the transfer of the Cry1F protein present in Bt maize to Spodopterafrugiperdadescendants, as well as this protein action in predation capacity and eficienty of Oriusinsidiosus e Doruluteipes, assessing the compatibility of these entomophagous agents use for S. frugiperdaresistant to the protein Cry1F. Resistant and susceptible neonates larvae to the protein Cry1F, were fed with non-Bt maize for ten days, and after that with Bt TC1507 ® maize, which expresses the Cry1F protein until the end of the larval development phase. Four treatments were studied a) Resistant larvae to the Cry1F protein with both sex exposed to the same protein, b) Resistant larvae with only the male exposed to Cry1F, c) Resistant larvae with only the female exposed to Cry1F, and g) susceptible larvae non-exposed to the protein, acting as control treatment. Detection and quantification of the Cry1F protein was performed by the Elisa test according to the Agdia® Kit protocol. The search time and capacity of predation of S. frugiperda eggs resistant to Cry1F protein were determined for nymphs of first, third and fifth instars for O. insidiosus and first, third and fourthfor D. luteipes. For the evaluation of neonates were determined for nymphs of third and fifth instars for O. insidiosus and third and fourthfor D. luteipes. As control, eggs and larvae of the susceptible S. frugiperda were used. To determine the search time, a triggered timer was used until the capture of the first prey and the predation capacity by counting the remaining prey after 24 hours. For the injury evaluation experiment, the maizeTC1507 and the isogenic conventional maize TC1507 were used as control, matching the Bt or conventional maize with five neonates larvae and one predator O. insidiosus and/or D. luteipes per plant. The injuries were assessed 7,14 e 21 days after larvae infestation, with scale of injuries with notes from one to five. Larvae were found to uptake Cry1F expressed in Bt maize and transferred it into the eggs. When both parents were exposed to the protein, the amount of protein identified in the eggs was higher. The amount of Cry1F detected in the eggs was smaller when just one parent was exposed. The predators were not able to distinguish between resistant preys or susceptible preys on the two evaluated phases (eggs and larvae) considering search time and consume. As for the injuries, where there was predator presence, the grade was significantly smaller than in the absence. Therefore, the use of predators promoted a decrease of larvae injury even when it was resistant to the Cry1F protein, being, this way, an instrument for resistance pest management.